STUDI KASUS: PENATALAKSANAAN ASFIKSIA SEDANG PADA BAYI BARU LAHIR DENGAN TEKNIK HAIKAP DI RSU AL-FATAH AMBON - Hasnawati Nukuhaly; Kasmiati Kasmiati (Poltekkes Kemenkes Maluku, 2023)
Newborn deaths are caused by spontaneous and regular breathing failure immediately after birth, asphyxia is the second highest cause of neonatal death, which is 27%. The purpose of the case study was to find out the management of moderate asphyxia newborns, this case study was conducted at the AL-Fatah Hospital in Ambon. Mrs. X's baby who experienced mild asphyxia was given care by warming, positioning, sucking mucus, drying, positioning, assessing (HAIKAP) by paying attention to the baby's airway, stimulating his breathing reflexes, and maintaining the baby's body temperature. Which gave positive results with an increase in the Apgar Score to normal. So it is very important for a midwife to be able to manage newborns with asphyxia according to evidence-based.